Od lojalności wspólnotowej do zindywidualizowanej. O ewolucji lojalności wśród pokoleń pracowników w korporacjach krakowskich = From Community Loyalty to Individualized Loyalty. Evolution of Loyalty among Generations of Corporate Employees in Cracow - Tomanek, Krzysztof (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Employee loyalty to the employer undergoes dynamic changes. This phenomenon takes various forms, in particular in complex organizational structures such as corporate culture. In contemporary discussions on the issue the loyalty does not only mean profit multiplication or observing the code of work ethics.
Keywords: lojalność; lojalnoś pracowników; korporacja; generacja Y; generacja X; pokolenie X; pokolenie Y; Kraków (woj. Małopolskie)